The fiscal body of sovereignty: to 'make live' in Indian country. (1st October 2016) - Pasternak, Shiri
ABSTRACT: Fiscal relations between the state and Indigenous peoples in Canada are a matter of life and death. By bringing to light techniques of economic rationality and governance of Indigenous peoples, this paper demonstrates a vital, yet overlooked trajectory in an ongoing colonial war. I examine specifically how Canada investigated and intentionally distorted Attawapiskat Chief Theresa Spence's band finances as a way to discredit her demands that governments respect her community's treaty rights. Further, I will analyze how these economic mechanisms and discourses functioned to 'settle' Indigenous territorial demands for self-determination in order for states and private industry to gain valuable access to Indigenous lands and resources. A multi-million dollar De Beers diamond mine operates 90 kilometers west of the Attawapiskat reserve and serves as an important site for examining how colonial forms of fiscal warfare work. For the past two centuries, an expectation of 'self-sufficiency' has been demanded from Indigenous peoples in tension with state investment in the dispossession of Indigenous lands; this tension defines Crown-Indigenous fiscal relations to this day and has been amplified recently in public discourses demanding accountability and transparency from Indigenous peoples while simultaneously decrying their dependency on the state. These discourses have developed in distinct relation to the conjoined historical and structural imperatives of settler colonial governance: territorial possession and resource access. I propose that by surveying the recent economic history of a resource periphery such as Attawapiskat First Nation, we may examine the kinds of power invested and produced in governing the lives and deaths of Indigenous peoples in Canada today.